proszę od[powiedź na teraz!
2(x+-2) = -(2x+1)
x-2 = 1/3 x +1
0,2x+ 0,3= -1,3



Odpowiedź :

Odpowiedź:

2(x+-2) = -(2x+1)

2x - 4 = -2x - 1

2x + 2x = -1 + 4

4x = 3       /:4

x = 3/4

x-2 = 1/3 x +1

x - 1/3x = 1 + 2

2/3x = 3      /*3/2

x = 3 * 3/2 = 9/2 = 4 1/2

0,2x + 0,3 = -1,3

0,2x = -1,3 - 0,3      /:0,2

x = -1,6/0,2 = -8

Szczegółowe wyjaśnienie:

2(x+-2) = -(2x+1)

2x-4=-2x-1

2x+2x=4-1

4x=3/:4

x=3/4

x-2 = 1/3 x +1

x-1/3x=1+2

x-1/3x=3/*3

3x-x=9

2x=9/2

x=4,5 albo x= 4 1/2

0,2x+ 0,3= -1,3

0,2x=-1,3-0,3

0,2x=-1,6/0,2

x=-8